Improved understanding of meanings of modal verbs in Legal English and increased motivation through Computer Assisted Language Learning - Đorđević, Jasmina (Ibérica (Castellón de la Plana, Spain), 2020)
This research explores the impact of Computer Assisted Language Learning (CALL) on the understanding of meanings of modal verbs in Legal English (mmvLE) and the level of motivation in an English for Specific Purposes (ESP) course. The hypothesis is that the understanding of the mmvle and the level of motivation will be increased if esp students are allowed to choose call as a preferred learning environment. Based on a quasi-experiment, the control group received instruction in a conventional classroom (CC) (face-to-face instruction, white board and paper-based material) and the experimental group received instruction in a call environment (combination of face-to-face and online instruction, web-facilitated). Following the principles of a repeated measures research design, the participants’ understanding of the mmvLE was measured in four subsequent instances. The detailed quantitative and qualitative error analysis shows that the CALL group outperformed the CC group. The analysis of the participants’ answers to the additional questionnaire completed at the beginning and at the end of the experiment as well as the group discussion after the experiment confirmed that call positively affected the participants’ motivation toward the subject matter